Analisis Kemampuan Pemecahan Masalah Matematis Siswa SMP dalam Menyelesaikan Soal Cerita - SRI NURHASANAH; Novi Andri Nurcahyono; Yanti Mulyanti (Jurnal Padegogik, 2023)
The purpose of this study is to analyze mathematical problem-solving abilities based on Polya's steps and the causes of students' errors in solving mathematical problems. The problem-solving stage consists of 4 stages, namely the stage of understanding the problem, planning a solution, carrying out a solution plan, and looking back. This study used 3 subjects from 30 eighth grade students of SMP Negeri 1 Curugkembar. Data collection is done by tests and interviews. The subject taking technique is purposive sampling. The data analysis used is the Miles and Hubberman model in this data analysis stage consisting of data collection, data reduction, data presentation, and drawing conclusions. The results of this study are (1) For students in the good category can understand the problem correctly in working on number pattern word problems, can make a settlement plan and are able to carry out according to the stages of solving the problem correctly and can also make conclusions from the answers obtained. (2) For students in the moderate category, they are quite good at understanding the questions, but sometimes they forget to write down one of the things that are known or asked about the number pattern story problems being worked on, in making a solution plan, the formula/equation used is usually not in accordance with what done in the process of carrying out the plan. Medium category students can also make conclusions from the answers they get. (3) For students who are in the low category cannot carry out problem solving steps such as understanding the problem, preparing a settlement plan, implementing a settlement plan and making conclusions on solving number pattern word problems.